The framing of political messages in Ayinla Omowura’s song-texts (2016)
Studies on African popular music have revealed that African musicians engage in political discourse which they deploy to reconstruct nationhood. There is no doubt that popular indigenous musical genres, especially those that were prominent at one time in the past, have been given insufficient attention in research studies by African scholars. Many of these studies have been driven especially by social responsibility theory, hegemony and counter-hegemonic theories and so on. However, this study using framing theory and textual analysis approach, examined the political themes described in Ayinla Omowura’s song texts of Orin owo'le Eko (Lagos Rent Edit), Ire wole de (Udoji Salary Increase), National Census, Eyin Oselu wa (Our Politicians), Challenge Cup and Late Murtala Mohammed. Findings reveal that Lagos rent edict, Udoji salary increment report, 1973 national census, politicians’ attitudes to elections, new currency introduction and 1972 change in the driving System are the dominant political events in the songs. Moreover, the social realities described include militarism, insufficient basic amenities, unemployment, policy implementation, hooliganism and electoral violence, rule of law, political dass wrangling, among others. In addition, government and political leaders were mostly portrayed as benefactors, while masses were sometimes counseled, or mildly reprimanded by the musician. In conclusion, though the events described in the selected songs happened in the 1970's in Nigeria, these themes still feature in the country's socio-political realities and are germane to political discourses in the twenty-first Century Nigeria